MANUSCRIPTS AND PUBLICATIONS OF THE POEM "MAKHZAN UL-ASROR" - Eshonqulova Feruza Husniddin qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article provides a comprehensive analysis of the distribution, preservation, and publication of Haydar Khwarazmi’s poem Makhzan ul-Asror. The study explores the various manuscript copies written in Uyghur and Arabic scripts, housed in major libraries and institutions worldwide, including Istanbul, London, Vienna, Paris, New York, Dublin, Budapest, Toronto, and Kazan. The article examines the different calligraphic styles, miniatures, decorative elements, and textual variations found across these editions. Additionally, the research compares multiple publications of the poem, such as those in the Anthology of Uzbek Literature, Echo of Centuries, and Blessed Letters. Furthermore, scholarly investigations into Makhzan ul-Asror and its influence on classical Uzbek literature are discussed, shedding light on its textual evolution and historical significance.